DAMPAK KEJAHATAN (TRAFFIKING) TERHADAP PEREMPUAN DAN ANAK DITINJAU DARI HUKUM INTERNASIONAL - Rindang Rizki Fitri; Abdul Rahman; Chairul Bariah (Journal of USU International Law, 2013)
Abstrak Trafficking is a labor export activities, the activities move someone from the neighborhood or relatives do keluarga.meskipun the permission of the concerned workers and families, trafficking is the trafficking in persons, especially women and anak2 with threats of violence and other forms of coercion, by way of deceptive , to deceive the victim of abuse of power, taking advantage of ignorance, innocence of the victim with the purpose of exploitation, especially exploitation of labor and sexual exploitation.law discriminated against trafficking in Indonesia in uu 39/1999 which stated in Article 297 of the Criminal Code, chapter 65 uu ham 39/1999, the international labor organization conventions and their implementation according to international labor organization convention 182.Keywords:Traffiking, Perdagangan, Tenaga Kerja , Perempuan dan Anak